Environmental Barriers Experienced by People With Spinal Cord Injury Across 22 Countries: Results From a Cross-Sectional Survey - Jan D. Reinhardt (2020)
© 2020 American Congress of Rehabilitation Medicine Objectives: To investigate the experience of environmental barriers by people with spinal cord injury (SCI) across 22 countries. Specific aims were to describe and compare the prevalence of environmental barriers experienced across countries, and to analyze determinants of environmental barriers at individual and country level. Design: Cross-sectional community survey. Participants: Individuals (N=12,591) living with SCI in the community. Interventions: Not applicable. Main Outcome Measure: Nottwil Environmental Factors Inventory–Short Form. Results: Most barriers were experienced in relation to accessibility, climate, transportation, finances, and state services. More severe barriers were experienced in settings with lower gross domestic product (GDP), which especially refers to medical supplies (gamma=–0.38; P<.001) and finances (gamma=–0.37; P<.001) in this study. However, in a multivariable negative binomial regression using within-between estimation of the number of barriers experienced on the selected predictors, the effect of GDP was reversed when it was adjusted for covariates. On the individual level, the number of experienced barriers decreased with better mental health and greater self-care ability. People with low income, with paraplegia, complete lesions, and more health problems reported more barriers. On the country level, fewer barriers were reported in countries with higher average age, better mental health, and greater self-care ability, as well as in those with a higher percentage of traumatic SCI, paraplegia, and complete lesions. More barriers were reported in countries with a higher percentage of married individuals, lower average household income, higher average time since injury, higher mean vitality scores, and greater income inequality. Conclusions: Study participants reported a significant number of environmental barriers, many of which are modifiable. Complementary interventions are recommended. Within and between country effects of covariates sometimes pointed in different directions, suggesting that countries with a different composition of SCI population also differed in environmental contexts.